(untitled) (Northern International Medical College Journal, 2018)
Background : There are various surgical options for management of anorectal malformations (ARM). Colostomy is a common part of the management of high anorectal malformation in the pediatric population. Objective : The aim of this study was to find out the most common complications after formation of divided sigmoid colostomy. Methods : This prospective observational study was done in the Division of Pediatric Surgery, Bangladesh Institute of Child Health and Dhaka Shishu (Children) Hospital, Dhaka from January 2012 to December 2017. Divided and separated sigmoid colostomy was doneon 116 patients admitted with ARM during this period. Follow up on 2nd, 4th and 8th week after operation was done and in each follow up patients were assessed clinicallyfor wound infection, skin excoriation, prolapse of colostomy, retraction of colostomy and parastomal hernia. If colostomy complications were found then managed as per standard method. Results : The mean age of patients was 2.43±1.29 days and majority of the patients 66 (56.9%) were male.About half of the patients 50(43.1%) had fistula and 21(18.1%) patients had associated anomaly. Among 116 patients 51 (43.97%) developed complications after colostomy. The most common complication was skin excoriation found in 35 (30.2%) patients followed by wound infection in 8(6.9%). Prolapse and retraction of colostomy was found only in 6 (5.17%)and 2 (1.7%) cases respectively. No patient developed parastomal hernia and there was no mortality. Conclusion : Divided and separated sigmoid colostomy provided satisfactory outcome in the management of high anorectal malformation. Skin excoriation was the most common complication and few developed wound infection and prolapse of colostomy. Northern International Medical College Journal Vol.9(2) Jan 2018: 311-314